Orienting the Training of Teachers in the Use of ICT: The Diagnosis Digital Skills Tree - Domínguez Hernández, José Antonio; Ruiz-Velasco, Enrique; Bárcenas, Josefina; Santos Tolosa, José (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2016)
One of the major problems facing education today lies in the fact that teachers are suddenly invaded for computers and forced to use them, also mobile devices and the Internet in the classroom. The lack of effective training programs and teacher training in the use and application of ICT in teaching and learning processes, has become a major problem that reaches almost all educational levels. In such a scenario, this paper proposes adoption by teachers, of a tool that will be useful to guide their training in the field of ICT: "The diagnosis digital skills tree," which provides an overview generally about computer and web resources that we have identified as relevant in the practice of teaching. This "diagnosis tree" is the result of a process of evaluation and monitoring conducted with groups of teachers who already use the technology in their teaching; and it is intended to guide and facilitate independent learning of teachers who are new to the use of ICT.